Early complications associated with obesity following coronary artery bypass graft surgery: Obesity and post-CABG morbidity - Mohammed, Amanj K.; Nadr, Jivara Hama (Journal of the Faculty of Medicine Baghdad, 2022)
Background: One of the major health concerns and possible risk factors in open heart surgery is the increasing prevalence of obesity among patients.Methodology: Over a period of sixteen months (February 2017 to June 2018), 246 patients underwent coronary artery bypass graft surgery (CABG) in Slemani Cardiac Hospital (SCH). The patients were divided according to the WHO classification into two groups: The obese (BMI ≥ 30) and the non-obese  (BMI < 30) and were compared in regard to the rate of occurrence of early postoperative complications.Objective: To evaluate the impact of obesity [body mass index (BMI) ≥ 30 Kg/m2] on the early post-operative (coronary artery bypass graft surgery) outcome.Results: The mean age was 69.0 years in the non-obese and 58 years in the obese group. Females constituted 46.7% of the obese group and 33.1% of the non-obese group. Both groups nearly got similar ejection fraction percentage of 58%, while hypertension was observed in 36.4% and 38.8% of the obese and non-obese groups respectively. Diabetes mellitus (DM) was reported in 54.2% of obese vs. 39.5% of non-obese patients. Cardiopulmonary bypass (CPB) time (72 min), aortic cross clamp time (59 min), mean perfusion pressure (67 mmHg) and number of grafts (3) were the same in both groups. Atelectasis rate (6.5%) and chest infection (5.6%) were significantly increased in obese patients. In contrast, other early post-operative complications were not statistically associated with being obese.Conclusion: There was a higher prevalence of obesity in referred patients for CABG as well as an increased rate of early post-operative complications in the obese.